Vulnerabilidad y riesgo por inundación en San Cristóbal de Las Casas, Chiapas - Montoya Gómez, Guillermo; Hernández Ruiz, José Francisco; Castillo Santiago, Miguel Ángel; Díaz Bonifaz, Diego Martín; Velasco Pérez, Alfredo (El Colegio de México A.C., 2008)
Some productive schemes and certain urbanization processes tend to configure structures with high negative externalities that undermine environmental equilibria and encourage climate changes throughout the world by triggering perverse cycles that affect the population living in vulnerable areas posing a variety of risks and threats that translate into social and economic alterations. This text presents the results observed in San Cristobal de las Casas after research was conducted in the neighborhoods located on the riverbanks using a digital elevation model and applying surveys. The study determined housing characteristics, inhabitants’ income levels and the degrees of vulnerability and risk to which they are exposed.